Comparison of the characteristics of long-term users of electronic cigarettes versus nicotine replacement therapy: A cross-sectional survey of English ex-smokers and current smokers. (1st August 2015) - Nelson, Victoria A.; Goniewicz, Maciej L.; Beard, Emma; Brown, Jamie; Sheals, Kate; West, Robert; Shahab, Lion
Highlights: E-cigarette (EC) and nicotine replacement therapy (NRT) are used for harm reduction. But little comparative data on their long-term use in smokers and quitters exist. We find that long-term EC users have stronger smoker identities than NRT users. EC users rate their product more highly and have lower intentions to stop use. In long-term quitters, withdrawal symptoms are reduced in EC compared with NRT user. Abstract: Background: Electronic cigarettes (ECs) and nicotine replacement therapy (NRT) are non-combustible nicotine delivery devices being widely used as a partial or a complete long-term substitute for smoking. Little is known about the characteristics of long-term users, their smoking behaviour, attachment to smoking, experience of nicotine withdrawal symptoms, or their views on these devices. This study aimed to provide preliminary evidence on this and compare users of the different products. Methods: UK participants were recruited from four naturally occurring groups of long-term (≥6 months) users of either EC or NRT who had stopped or continued to smoke ( N = 36 per group, total N = 144). Participants completed a questionnaire assessing socio-demographic and smoking characteristics, nicotine withdrawal symptoms, smoker identity and attitudes towards the products they were using. Results: Adjusting for relevant confounders, EC use was associated with a stronger smoker identity (Wald X 2 (1) = 3.9, p = 0.048) and greater product endorsement (Wald X 2 (1) = 4.6, p = 0.024) than NRT use, irrespective of smoking status. Among ex-smokers, EC users reported less severe mood and physical symptoms (Wald X 2 (1) = 6.1, p = 0.014) and cravings (Wald X 2 (1) = 8.5, p = 0.003), higher perceived helpfulness of the product (Wald X 2 (1) = 4.8, p = 0.028) and lower intentions to stop using the product (Wald X 2 (1) = 17.6, p < 0.001) than NRT users. Conclusions: Compared with people who use NRT for at least 6 months, those who use EC over that time period appear to have a stronger smoker identity and like their products more. Among long-term users who have stopped smoking, ECs are perceived as more helpful than NRT, appear more effective in controlling withdrawal symptoms and continued use may be more likely.